Penerapan Model Reverse Jigsaw dalam Meningkatkan Keterampilan Berbicara pada Pembelajaran Bahasa Inggris - Bambang Siswoyo; Roro Erna Sri Ratnawati; Desi Mislianti; Kurnia Atiullah; Heny Maryana; Yunita Budi Cahyani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The purpose of this study is to describe the procedures, advantages, and disadvantages of implementing the Reverse Jigsaw learning model in English language This study employs a qualitative approach. The research subjects were English teachers at the aforementioned institutions. Data collection techniques included interviews, observations, and documentation. The results of the study show: 1) The steps of the Reverse Jigsaw model involve forming heterogeneous home groups of 4–6 members, assigning different tasks to each member, grouping students with the same tasks into expert groups to discuss the material, returning to mixed groups where each student is given a case study with several questions or one complex question and around 15 minutes to work on it. Each team member is assigned a unique topic, followed by discussion and note-taking in mixed groups. Students then regroup into expert/topic groups to compare discussion results, typically within 15–20 minutes. Finally, representatives from each expert group present their findings to the entire class. 2) The advantages of the Reverse Jigsaw model include promoting peer collaboration, enhancing students' academic abilities, enabling peer-to-peer learning, encouraging the generation of new ideas, and boosting self-confidence. 3) The disadvantages include varying perceptions in understanding the discussed concepts, requiring considerable time and thorough preparation, and difficulties in convincing students to present material to their peers if they lack confidence.